Pengembangan Media Pembelajaran Interaktif Digital untuk Meningkatkan Keterampilan Proses Sains Siswa Kelas V dalam Pembelajaran IPAS di SDN Resongo 1 - Muhammat Mubin; Ludfi Arya Wardana; Didit Yulian Kasdriyanto; Ryzca Siti Qomariah (CV. ITTC INDONESIA, 2026)
This study aims to develop valid, practical, and effective Canva-based interactive digital learning media to improve the science process skills of fifth-grade students in the Natural and Social Sciences (IPAS) course at SDN Resongo I. The development of this learning material was undertaken in response to the low level of students’ science process skills—which are still largely shaped by conventional teaching methods—as well as the limited use of interactive digital media that aligns with the characteristics of the Merdeka Curriculum. The study employed the Research and Development (R&D) method using the ADDIE model, which comprises the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of one subject matter expert, one media expert, one fifth-grade teacher, and 31 fifth-grade students at SDN Resongo I. Data were collected through observation, interviews, validation sheets, teacher and student response questionnaires, as well as pretest and posttest assessments. The results showed that the media received a feasibility rating of 97% from the media expert and 95% from the subject matter expert, both falling into the “highly valid” category. The teacher response rate reached 100%, while the student response rate was 90%, both falling into the “highly practical” category. The effectiveness test results showed an N-Gain value of 0.63, which falls into the “moderate” category, indicating that the media was able to significantly improve students’ science process skills. Thus, the Canva-based interactive learning media is suitable for use as a